Retrospective analysis of clinical characteristics and treatment of children and adolescents with depression - Jiang, Xiaolu; Zheng, Hongyu; Yang, Rong; Wang, Shuo; Zhong, Hui (Frontiers in Psychiatry, 2023)
Objective To analyze the demographic and clinical characteristics and treatment among children and adolescents with depression in different age groups of onset. Methods 635 children and adolescents with depression in a hospital from January 2014 to December 2021 were collected by e-case, and grouped according to age of onset, including 115 cases in childhood 8-12, 359 cases in early adolescence 13-1 and 161 cases in late adolescence 16-18, and the general conditions, clinical characteristics, and treatment were compared between the three groups. Results Females had more onset and were more likely to have psychotic symptoms in childhood, short duration and hospitalization in early adolescence increased year by year, and males had more onset and less hospitalization in late adolescence. There were no statistical differences in medication regimen, suicide, length of hospitalization, or family history between the three groups. Conclusion Children and adolescents with depression have their unique clinical characteristics at different age of onset and need to enhance prevention and individualized treatment.